The barriers and facilitators to implementing dementia education and training in health and social care services: a mixed-methods study - Claire A. Surr; Sahdia Parveen; Sarah J. Smith; Michelle Drury; Cara Sass; Sarah Burden; Jan Oyebode (BMC, 2020)
Abstract Background The health and social care workforce requires access to appropriate education and training to provide quality care for people with dementia. Success of a training programme depends on staff ability to put their learning into practice through behaviour change. This study aimed to investigate the barriers and facilitators to implementation of dementia education and training in health and social care services using the Theoretical Domains Framework (TDF) and COM-B model of behaviour change. Methods A mixed-methods design. Participants were dementia training leads, training facilitators, managers and staff who had attended training who worked in UK care homes, acute hospitals, mental health services and primary care settings. Methods were an online audit of care and training providers, online survey of trained staff and individual/group interviews with organisational training leads, training facilitators, staff who had attended dementia training and managers. Data were analysed using descriptive statistics and thematic template analysis. Results Barriers and facilitators were analysed according the COM-B domains. "Capability" factors were not perceived as a significant barrier to training implementation. Factors which supported staff capability included the use of interactive face-to-face training, and training that was relevant to their role. Factors that increased staff "motivation" included skilled facilitation of training, trainees' desire to learn and the provision of incentives (e.g. attendance during paid working hours, badges/certifications). "Opportunity" factors were most prevalent with lack of resources (time, financial, staffing and environmental) being the biggest perceived barrier to training implementation. The presence or not of external support from families and internal factors such as the organisational culture and its supportiveness of good dementia care and training implementation were also influential. Conclusions A wide range of factors may present as barriers to or facilitators of dementia training implementation and behaviour change for staff. These should be considered by health and social care providers in the context of dementia training design and delivery in order to maximise potential for implementation.